Comparison of different microwave methods for unburned carbon content in fly ash determination. (June 2019) - Peng, Fan; Niu, Yuguang; Gao, Kai; Gai, Xinhua; Dai, Li; Geng, Lina
Highlights: An accuracy of 0.2% can be realized with waveguide method in low UC content (0–2%) detection. The waveguide method is superior to the free space method in terms of measurement accuracy. The accuracy of using the magnitude as the measurement parameter is lower than that of using the phase. Abstract: To compare the performances of different microwave measure methods in UC content determination, we have developed two measurement systems that can be operated in 12–15 GHz band, including one based on free space method, and the other based on waveguide method. The fly ash samples with UC content in 0–20% are measured. In addition, this paper specifically studies the test results in the 0–2% low UC content range using the waveguide method. The measurement range and measure accuracy are analyzed to evaluate these methods. For measurement range, free space method can realize wider measurement range of UC content compared with waveguide method. For accuracy, the error of UC content is used as an accuracy indicator to evaluate accuracies under different test modes. The calculated accuracy indicators can verify the following conclusions. The waveguide method is superior to the free space method and the accuracy of using the magnitude as the measurement parameter is lower than that of using the phase in both measurement systems.